Clinical Practice Guidelines for Severe Chronic Obstructive Pulmonary Disease. - Niurka Mercedes Galende Hernández; Diosdania Alfonso Falcón; Carlos Alberto Martell Alonso; Alexis Díaz Mesa; Inti Santana Carballosa (Medisur)
Clinical Practice Guidelines for Severe Chronic Obstructive Pulmonary Disease. This concept includes simple chronic bronchitis, asthmatic bronchitis, chronic obstructive bronchitis, and pulmonary emphysema; although this two last are the most commonly included. Risk factors, classification and treatment are commented, stressing the strategy of mechanical ventilation and the indications for mechanical invasive and no invasive ventilation. It includes assessment guidelines focused on the most important aspects to be accomplished.